STUDENTS PERCEPTIONS OF IMPLEMENTING ONLINE LEARNING IN INTEGRATED SCIENCE SUBJECTS IN CLASS VIII AT SMPN 1 SUKATANI - Syifa Fauziah (JURNAL ASIK, 2025)
This study aims to determine students' perceptions of the implementation of online learning in Integrated Science subjects in class VIII of SMPN 1 Sukatani. Online learning that has been implemented since the COVID-19 pandemic has its own challenges and advantages in the teaching and learning process, especially in subjects that are practical in nature such as Integrated Science. Student perceptions are an important factor that influences the effectiveness of learning, both in terms of understanding the material, interaction with teachers, and the use of technology. This study uses a qualitative method with a descriptive approach. Data were collected through questionnaires and interviews with 30 students of class VIII of SMPN 1 Sukatani who took part in online Integrated Science learning. The results showed that most students had a positive perception of the flexibility of time offered by online learning, but there were still complaints about the difficulty in understanding the material presented online, especially on topics that require experiments or practicums. In addition, factors such as limited technological facilities, such as inadequate devices and internet network constraints, also influenced students' perceptions. The interaction between students and teachers was considered less than optimal due to the limited time for direct discussion. However, students felt that online learning provided an opportunity for independent learning and accessing materials at any time. This study is expected to provide input for schools and teachers to optimize online learning by considering the needs and comfort of students in the Integrated Science learning process in the future.